PENGARUH VERMIKOMPOS TERHADAP KANDUNGAN KADMIUM DAN FASE VEGETATIF TANAMAN PADI GOGO DI INCEPTISOL - Kartika Utami; Agus Ardiansyah; Priyono Prawito; Zainal Muktamar (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Heavy metal pollution is an important issue that must receive serious attention from various authorities, including the community. Cadmium (Cd) contamination will harm environmental and human health. Upland rice plants are the main food-producing plants susceptible to Cd contamination. This study aimed to determine the effect of vermicompost on cadmium content and the vegetative phase of upland rice plants in Inceptisol. This study used a Completely Randomized Design (CRD) with one factor, namely several dose levels of vermicompost, namely 0, 5, 10, 15, 20, and 25 t ha-1. The results of this study indicated that the use of vermicompost significantly affected the number of leaves and tillers of upland rice. A Vermicompost dose of 15 t ha-1 is considered optimum in increasing the number of leaves and tillers of upland rice. The use of vermicompost increased the vegetative growth of upland rice, so it increased the productivity of upland rice plants.